A Review of the Conversational Pragmatic Skills of Children With Cochlear Implants. (17th March 2021) - Crowe, Kathryn; Dammeyer, Jesper
Abstract: Many children who use cochlear implants (CI) have strong skills in many aspects of spoken language; however, limited information is available about their mastery of the pragmatic skills required to participate in conversation. This study reviewed published literature describing the pragmatic skills of children who use CIs in conversational contexts. Twenty-five studies met the inclusion criteria, and data were extracted describing participant characteristics, methodology, data type, outcomes, and factors associated with outcomes. Pragmatic skills were described in three broad categories: speech acts, turns, and breakdowns and repairs. Participants showed heterogeneity in age, age at implantation, duration of implant use, and languages used. Studies employed a variety of methodologies, used a range of different sample types and coding strategies, and considered different factors associated that might be associated with children's pragmatic skills. Across studies, children with CIs were reported to have a range of pragmatic skills in conversational contexts, from few to severe difficulties. The body of literature on this topic is small and considered heterogeneous children with CIs with a wide range of skills. Further research is needed to understand the pragmatics language skills of children with CIs and the factors influencing the diversity in skills observed.